Work Experience as an Intermediary: The Influence of Work Motivation and Transformational Leadership on Teacher Performance - Liunokas, Adelina; Pranoto, Yuli Kurnawati Sugiyo; Formen, Ali (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to determine and analyze the effect of work motivation and transformational leadership on the performance of kindergarten teachers in Kupang City, with work experience as an intermediary variable. This type of research is descriptive quantitative research. A total of 190 kindergarten teachers who participated in this study were selected based on the Krejcie table with a significance level of 5%. This research instrument used a Google Form questionnaire. Hypothesis testing uses a normality test, significance test, linearity test, multicollinearity test, heteroscedasticity test, coefficient of determination test, and Sobel test. The results of this study indicate that better work motivation and the application of transformational leadership can improve teacher performance through work experience. With good work motivation from a teacher, it will be a driving force in improving teacher performance. The better a principal who applies aspects of transformational leadership well can create a supportive work environment to increase teacher effectiveness. Work experience is also an important factor in improving teacher performance, where teachers who are new to teaching show better performance in matters related to current topics of various general knowledge. Principals are advised to support training and professional development programs for teachers so that they can share experiences that then improve teacher performance. For further research, it is expected to explore other factors that affect teacher performance.